Estimation of the convergence rate in central limiting theorem for two-parametric martingale-differences - Koval , T. L. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We present an estimate of the rate of convergence to the normal law of the least squares estimator of the regression coefficient for a random field which is a two-parameter martingale difference sequence.